Future climate warming increases Greenland ice sheet surface mass balance variability - Fyke, J.G. (author); Vizcaino, M. (author); Lipscomb, W. (author); Price, S. (author) (Geophysical Research Letters, 2014)
The integrated surface mass balance (SMB) of the Greenland ice sheet (GrIS) has large interannual variability. Long-term future changes to this variability will affect GrIS dynamics, freshwater fluxes, regional oceanography, and detection of changes in ice volume trends. Here we analyze a simulated 1850–2100 GrIS SMB time series from the Community Earth System Model, currently the only global climate model that realistically simulates GrIS SMB. We find a significant increase in interannual integrated SMB variability over time, which we attribute primarily to a shift to a high-variability melt-dominated SMB regime due to GrIS ablation area growth. We find temporal increases to characteristic ablation and accumulation area-specific SMB variabilities to be of secondary importance. Since ablation area SMB variability is driven largely by variability in summer surface melt, variability in the climate processes regulating the energy fluxes that control melting will likely increasingly determine future GrIS SMB variability. Geoscience & Remote Sensing Civil Engineering and Geosciences